The Impact of Chemotherapy on Dietary Status as Well as Life Quality in Kids with Cancer in Belgium - Patrick, Dr. Jean (American Journal of Food Sciences and Nutrition, 2023)
Purpose: The purpose of this study was to evaluate the impact of chemotherapy on dietary status as well as life quality in kids with cancer in Belgium. Methodology: The study used a desktop literature review methodology (desk study). This required a thorough analysis of research on the impact of chemotherapy on dietary status as well as life quality in kids with cancer. The subject of the study underwent three phases of sorting in order to assess its suitability for further study. Findings: This study concluded that chemotherapy was associated with poor dietary status and reduction in the life quality ratings. The use of the Nutrition Impact Symptom (NIS) checklist in the kid's oncology clinic/ward triggers more therapeutic interventions. The awareness for NIS will likely evoke more research in assessment, impact, and treatment. Unique Contribution to Theory, Practice and Policy: This study recommended that individual's food preferences and aversions should be considered and combinations of oral, enteral and parenteral diet be provided. In view of the findings, the study recommends that dietetics should frequently carry out diet assessments in order to provide proper management to curb malnutrition.